Analisis Pembelajaran Sejarah dengan Materi Islam Untuk Meningkatkan Kesadaran Pendidikan Multikultural di SMA Negeri 11 Medan - Sardiana, Siti; Nababan, Surya Aymanda; Saragih, Ridho Gilang Amalsyah (Medan Resource Center, 2023)
Multicultural education is becoming increasingly important in heterogeneous societies like Indonesia. One subject that has the potential to implement multicultural education is history, particularly when studying Islamic history. Indonesia is a region with diverse cultural backgrounds, often referred to as multicultural. This diversity is also present in the field of education. This research aims to explain or analyze history lessons with Islamic content to enhance awareness of multicultural education in SMA Negeri 11 Medan, specifically considering the cultural backgrounds of students who adhere to different religions, which can potentially trigger conflicts within a multicultural community. Therefore, multicultural education is expected to serve as a foundation for prioritizing tolerance in society, especially among students in schools. This research utilizes qualitative research methods with a case study approach to analyze how multicultural education is integrated into history lessons at school. This is related to the study of history, which explores the nature and habits of humanity over time. The connection between multicultural education and history education is valuable in fostering multicultural awareness and uniting various differences, enabling peaceful and harmonious coexistence, especially among students in schools. The research findings indicate that the analysis of multicultural education in history lessons with Islamic content at SMA Negeri 11 Medan has been conducted effectively. History researchers employ various approaches and strategies that consider the diversity of students. They explore diverse Islamic historical sources and utilize methods such as discussions, group assignments, and field activities to enhance students' understanding of Islamic history. Additionally, collaborative efforts between teachers, schools, and relevant stakeholders are necessary to create an inclusive learning environment that supports the diversity of students.